Neurexin-Neuroligin Trans-Synaptic Interaction Mediates Learning-Related Synaptic Remodeling and Long-Term Facilitation in Aplysia - Choi, Yun-Beom (2011)
Neurexin and neuroligin, which undergo heterophilic interactions with each other at the synapse, are mutated in some patients with autism spectrum disorder, a set of disorders characterized by deficits in social and emotional learning. We have explored the role of neurexin and neuroligin at sensory-to-motor neuron synapses of the gill-withdrawal reflex in Aplysia that undergoes sensitization, a simple form of learned fear. We find that depleting neurexin in the presynaptic sensory neuron or neuroligin in the postsynaptic motor neuron abolishes both long-term facilitation and the associated presynaptic growth induced by repeated pulses of serotonin. Moreover, introduction into the motor neuron of the R451C mutation of neuroligin-3 linked to autism spectrum disorder blocks both intermediate-term and long-term facilitation. Our results suggest that activity-dependent regulation of the neurexin-neuroligin interaction may govern trans-synaptic signaling required for the storage of long-term memory, including emotional memory that may be impaired in autism spectrum disorder.